The Institutionalisation and Commodification of the Mushaf Al-Qur'an in Indonesia: An Analysis of the Business Practices of Syaamil Quran - Muhammad Nur Hidayat; Eni Zulaiha (Jurnal Iman dan Spiritualitas, 2026)
This study examines the institutionalization and commodification of the Qur’anic mushaf within the business practices of Syaamil Quran in Indonesia, and explores how the sacredness of the text is continuously negotiated within contemporary market dynamics. Theoretical perspectives include Marx’s theory of commodification, Mosco’s content commodification, Baudrillard’s sign-value, Bourdieu’s symbolic capital, and Gauthier’s concept of spiritual capitalism. Employing a qualitative case study approach, data were collected through in-depth interviews, field observations, and document analysis. The study focuses on product innovation, aesthetic design, personalization, pedagogical features, and the construction of religious legitimacy within Syaamil’s publishing model. Findings reveal that the mushaf has evolved into a hybrid entity—simultaneously sacred and commodified—functioning not only as a religious text, but also as a cultural artifact, identity marker, and symbolic commodity. The principal challenge identified is the risk of commodity fetishism, in which aesthetic form and prestige may overshadow deeper spiritual engagement. This study recommends reinforcing ethical governance in religious publishing and sustaining collaboration with Islamic scholars to preserve the Qur’an’s transformative function in society. This study contributes to the field of religion and political economy by positioning the Qur’anic mushaf as an emergent site of negotiation between sacred meaning and capitalist rationality, offering a critical model for understanding religious publishing in modern Muslim societies.